The Impact of Patient Adherence to Dual Antiplatelet Medication Following Percutaneous Coronary Intervention on the Occurrence of Adverse Cardiovascular Events - Mansurova JA; Orekhov A; Zhunuspekova AS; Kassymova AA; Karazhanova LK (Patient Preference and Adherence, 2024)
J A Mansurova, Andrey Orekhov, A S Zhunuspekova, A A Kassymova, L K Karazhanova Department of Therapy, Non-Commercial Joint-Stock Company “Semey Medical University”, Semey, The Republic of KazakhstanCorrespondence: Andrey Orekhov, Department of Therapy, Non-Commercial Joint-Stock Company “Semey Medical University”, Molodogvardeyskaya 34-1 Street, Semey, F18E9T9, The Republic of Kazakhstan, Tel +87774141476, Email orekhov-andrei@list.ruBackground: The objective of this study is to examine the impact of medication adherence on the timing of non-cardiovascular serious events (NCDS) onset in patients with acute coronary syndrome (ACS) after percutaneous coronary intervention (PCI).Methods: This prospective study was conducted at a single center and involved 220 ACS patients who underwent sequential PCI with stenting. The Morisky Green Levine Medication Adherence Scale was employed to assess adherence to dual antiplatelet therapy (DAPT) and its impact on NCDS occurrence. Early in their hospitalization, all patients received education at the Coronary Heart Disease School. The survival rates of patients in both the main group and a control group (n=355) were subsequently evaluated.Results: The study findings indicated an inverse relationship between stent thrombosis development (Rho=− 0.334; p=0.001) and the timing of recurrent myocardial ischemia. There was also an inverse correlation between patient adherence and stent thrombosis development (Rho=− 0.275; p=0.009). Non-adherent individuals had a 16.8 times higher likelihood of experiencing stent thrombosis compared to compliant patients (p< 0.001). Following participation in the CHD School program, treatment adherence increased from 56.5% to 88.2%. Education for ACS patients post-stenting was significantly associated with all-cause mortality within the first 6 months (p=0.040).Conclusion: Secondary preventive measures, including education, impact the success of endovascular interventions in both the early hospital phase and the long term. Patient education can serve as a supplementary intervention to enhance DAPT adherence, thus diminishing the risk of recurrent cardiovascular events and mortality post endovascular intervention.Keywords: acute coronary syndrome, percutaneous coronary intervention, adherence, education, dual antiplatelet therapy